Phyllanthus tenellus Roxb. (Phyllanthaceae): A NEW RECORD TO THE FLORA OF SUMATERA - Muhammad Rifqi Hariri; Arifin Surya Dwipa Irsyam; Arieh Mountara (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
Phyllanthus is a genus with many members that are quite widespread throughout the world. Previously, this genus belonged to the Euphorbiaceae family but based on molecular studies it was separated into separate Phyllanthaceae families. Botanical explorations carried out on the islands of Bangka and Belitung indicated that Phyllanthus tenellus had not been recorded yet in Phyllanthus in Sumatra. Phyllanthus tenellus is a new alien plant record for the flora of Sumatra and increases the number of Phyllanthus species in Sumatra to 14 species. This species is thought to have been introduced accidentally and has naturalized in urban areas. A brief description, the factors causing the presence of this species in Sumatra, and their potential uses are described.